2004
DOI: 10.1080/00207450490269444
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Parkinson's Disease and Parkinsonism in a Colombian Population Using the Capture-Recapture Method

Abstract: Our objective was to estimate the prevalence of Parkinson's disease (PD) and Parkinsonism (Ps) in Antioquia (Colombia), using the Capture-Recapture method. The two biggest institutions for attending neurological patients in Antioquia were selected as sources for the use of the Capture-Recapture method. Prevalences of PD (PPD) and Ps (PPs) were estimated according to the following expression: PPD (or PPs) = n/Nl105. The number of cases (n) of PD (or Ps), n = a + b + c + d, where a = cases identified from the tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
7

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 9 publications
0
14
0
7
Order By: Relevance
“…In Colombia, the National Epidemiologic Study conducted between 1995 and 1996 reported a crude prevalence of 470/100 000 for PD [5], whilst in 2004, in the same country, Sánchez et al. [6] reported a crude prevalence of 30.7/100 000 and 176.4/100 000 in a population older than 50 years in the department of Antioquia. A community‐based study in Bambui, Brazil in a cohort older than 64 years showed a prevalence of 3300/100 000 [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Colombia, the National Epidemiologic Study conducted between 1995 and 1996 reported a crude prevalence of 470/100 000 for PD [5], whilst in 2004, in the same country, Sánchez et al. [6] reported a crude prevalence of 30.7/100 000 and 176.4/100 000 in a population older than 50 years in the department of Antioquia. A community‐based study in Bambui, Brazil in a cohort older than 64 years showed a prevalence of 3300/100 000 [7].…”
Section: Discussionmentioning
confidence: 99%
“…However, genetic and environmental factors may also contribute. Currently, there is no data regarding incidence of PD in South America, and only few studies have estimated the prevalence in select regions [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The CRM may be one of only a few techniques to accurately assess disease spread and frequency in developing countries like Thailand. This technique has been applied in many settings to estimate the distribution and prevalence of such disorders as type 2 diabetes, fetal alcohol syndrome and PD [14][15][16][17] .…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, data about HRQoL in South America, Africa, and Asia are scarce 11–13. In South America, specifically, most of the published papers about PD refer to epidemiological studies 14–16. Furthermore, data regarding the impact of PD in Brazil do not exist.…”
mentioning
confidence: 99%